PENCEGAHAN MODUS PELANGGARAN KODE ETIK PENYELENGGARA PEMILU DALAM PENETAPAN CALON KEPALA DAERAH - Arifudin Arifudin; Nurwidyanto . (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2021)
Determination of candidate at local election is an important stage in the process of democratic regional head election. In the process of determining the facts in Garut Regency Election Year 2018 raises a mode of violation of the code of ethics in the form of money politics. Therefore in this paper formulated the problem is: what factors causing the emergence of violation mode of ethics of election organizers in the determination of candidates for regional heads ?; and how prevention of violation mode of ethics of election organizers in the determination of candidates for regional head ?. In this paper it is concluded that the mode of violation of the code of ethics in the determination of the candidate pair of regional heads is not only caused by the conduct of the election organizer but also caused by the candidate's candidate and the success team that encourage the election organizers to violate the code of ethics. Therefore, an ethics education instrument is required for the candidate of regional head, pre verification of candidate pair of regional head, as well as sanctions for election organizers and prospective candidates of regional head has not been formulated in a legislation.